2014
DOI: 10.1007/s00248-014-0464-8
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Treatment Plant Effluents Change Abundance and Composition of Ammonia-Oxidizing Microorganisms in Mediterranean Urban Stream Biofilms

Abstract: Streams affected by wastewater treatment plant (WWTP) effluents are hotspots of nitrification. We analyzed the influence of WWTP inputs on the abundance, distribution, and composition of epilithic ammonia-oxidizing (AO) assemblages in five Mediterranean urban streams by qPCR and amoA gene cloning and sequencing of both archaea (AOA) and bacteria (AOB). The effluents significantly modified stream chemical parameters, and changes in longitudinal profiles of both NH(4)(+) and NO(3)(-) indicated stimulated nitrifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
33
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
10
33
0
5
Order By: Relevance
“…An alternative explanation is that the enrichment of NH 4 ? can favor the development of nitrifiers, which is supported by results from previous studies (Bernhardt and Likens 2004;Merbt et al 2015). Nitrifying microorganisms have lower growth efficiencies compared to other microbial components of the biofilms (Risgaard-Petersen et al 2004) and they also have a preferential demand for NH 4…”
supporting
confidence: 74%
“…An alternative explanation is that the enrichment of NH 4 ? can favor the development of nitrifiers, which is supported by results from previous studies (Bernhardt and Likens 2004;Merbt et al 2015). Nitrifying microorganisms have lower growth efficiencies compared to other microbial components of the biofilms (Risgaard-Petersen et al 2004) and they also have a preferential demand for NH 4…”
supporting
confidence: 74%
“…In fact, a similar mechanism has been proposed to explain sustained photoautotrophic activity under high irradiance in streams (Boston and Hill ; Guasch and Sabater ). In this line of thought, previous investigations carried out in the same stream sites showed Nitrosotalea devanaterra ‐like as dominant AOA in both, light‐side and dark‐side biofilms (Merbt et al ), a species strongly inhibited by light in experiments carried out in cultures (Merbt et al ). This fact suggests that light avoidance was the most likely strategy to overcome photoinhibition in natural biofilms.…”
Section: Discussionmentioning
confidence: 63%
“…). However, despite large differences in light availability and abundance of photoautotrophs, light‐side and dark‐side biofilms from a given location hosted similar AOA community composition (Merbt et al ). Based on these findings, we assumed that differences observed during incubation experiments between biofilms from the two sides of the cobbles for a given location were related to their physiological response to light conditions rather than to differences in the composition of AO communities.…”
Section: Methodsmentioning
confidence: 99%
“…Studies addressing the effect of flow intermittency on archaeal communities are scarce compared to those with bacteria, and this can be taken as an indication that Archaea constitute a minor component of streambed microbial communities. Even in permanent rivers and streams Bacteria outnumber Archaea in all streambed compartments (Battin et al, 2001;Herrmann et al, 2011;Merbt et al, 2011Merbt et al, , 2015Buriánková et al, 2013), but is also true that Archaea occur in arid soils, microbial mats and freshwater sediments exposed to desiccation (Rothrock and (Rothrock and Garcia-Pichel, 2005;Soule et al, 2009;Timonen and Bomberg, 2009;Conrad et al, 2014). Despite this information, no conclusive data on the ecological function of the Archaea in streambeds are available.…”
Section: Structural Changes and Adaptations Of Biofilms To Dry And Wementioning
confidence: 88%
“…Despite this information, no conclusive data on the ecological function of the Archaea in streambeds are available. Some studies have identified either methanogenic groups (Buriánková et al, 2013;Mach et al, 2015) or molecular signatures of ammonia oxidizing archaea (AOA; Merbt et al, 2011Merbt et al, , 2015 suggesting a relevant but not yet resolved contribution to C and N cycles, respectively. AOA are abundant in soils, where they play an outstanding role in nitrification (Stahl and de la Torre, 2012), but are less resistant to desiccation than ammonia oxidizing bacteria and less resilient to flow return, when ammonium concentrations are high (Thion and Prosser, 2014).…”
Section: Structural Changes and Adaptations Of Biofilms To Dry And Wementioning
confidence: 99%